Dielectric Study on Fly Ash Blended Cement. Issue 1 (2009) - Sivakumar, G.; Mohanraj, K.; Barathan, S.
Abstract : In this paper, the hydration behaviour of ordinary portland cement (OPC) and fly ash blended cement (10, 25 and 40%) replaced by two different fly ashes (FA) were investigated. The samples were hydrated with distilled water (DW) in water to solid ratio 0:4 and its setting time and dielectric measurement are carried out. Results of the study found that the fly ash blended cement composites have slow hydration than OPC during early stages (up to 24 h).